2016
DOI: 10.1371/journal.pone.0165483
|View full text |Cite
|
Sign up to set email alerts
|

Daesiho-Tang Is an Effective Herbal Formulation in Attenuation of Obesity in Mice through Alteration of Gene Expression and Modulation of Intestinal Microbiota

Abstract: BackgroundObesity has become a major global health challenge due to its increasing prevalence, and the associated health risk. It is the main cause of various metabolic diseases including diabetes, hypertension, cardiovascular disease, stroke and certain forms of cancer.Methods and ResultsIn the present study we evaluated the anti-obesity property of Daesiho-tang (DSHT), an herbal medicine, using high fat diet (HFD)-induced obese mice as a model. Our results showed that DSHT ameliorated body weight gain, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 68 publications
1
47
0
Order By: Relevance
“…Many studies have searched for effective herbal medicines for treating obesity and NAFLD [37,38]. Among the many candidates, DST has shown potential to treat obesity and NAFLD in many preclinical studies [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have searched for effective herbal medicines for treating obesity and NAFLD [37,38]. Among the many candidates, DST has shown potential to treat obesity and NAFLD in many preclinical studies [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Many animal studies have confirmed the anti-obesity, anti-diabetic and anti-hypertensive effects of DST [11][12][13][14]. Hussain et al reported that DST ameliorates body weight gain in mice fed a high-fat diet by regulating leptin and adiponectin gene expression in adipose tissue [11]. Authors of in vivo and in vitro studies have reported that DST improves lipid metabolism by lowering hepatic triglyceride biosynthesis and by increasing low-density lipoprotein receptor gene expression in hepatocytes [15,16].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, the anti-obesity property of daesiho-tang (DSHT) was also investigated. It was found that DSHT treatment significantly reduced serum TC and TG and hepatic fat accumulation which were associated with the regulation on abundance of gut microbiota [165]. Although the mechanisms underlying TCM are extremely complicated and largely unknown, gut microbiota was important target for many TCM formulas because many kinds of chemicals within TCM are unabsorbable that can influence gut microbiota directly or be metabolized into active form by gut microbiota.…”
Section: Gut Microbiota-targeted Therapies With Other Approachesmentioning
confidence: 99%
“…The probable mechanisms by which the gut microbiota could cause the onset and development of obesity and the related metabolic diseases include: (a) high abundance of carbohydrate-fermenting bacteria which leads to an increased production of short-chain fatty acids (SCFAs), providing an extra source of energy for the host in the form of stored lipids or glucose; (b) augmented intestinal permeability to bacterial lipopolysaccharides (LPS), resulting in elevated systemic LPS levels that trigger low-grade inflammation and insulin resistance; and (c) enhanced activity of the gut endocannabinoid system [23]. A number of our previous studies have shown that the protective effects of several herbal formulations against inflammatory insult and metabolic disorders are mediated via modulation of the gut microbial population [17,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%